UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAN FRAKSI N-HEKSAN, ETIL ASETAT DAN AIR KULIT BAWANG MERAH (Allium cepa L.)TERHADAP BAKTERI Escherichia coli - Lidia Klorida Br Barus (Fakultas Farmasi Institut Kesehatan DELI HUSADA Deli Tua, 2026)
Shallot peel (Allium cepa L.) is an agricultural waste that is known to contain secondary metabolite compounds such as flavonoids, alkaloids, tannins, and saponins that have the potential to have antibacterial activity. This study aims to determine the antibacterial activity of ethanol extract and the fraction of n-hexane, ethyl acetate, and water from onion peel against Escherichia coli bacteria. Extraction was carried out using the maceration method with 96% ethanol, then continued with liquid-liquid fractionation using n-hexane, ethyl acetate, and water. The antibacterial activity test was carried out using the disc diffusion method with concentrations of 40%, 60%, and 80%. The results showed that ethanol extract and shallot peel fractions had an inhibition against Escherichia coli, with the ethyl acetate fraction at a concentration of 80% indicating the largest inhibition zone. Thus, shallot peel has the potential to be developed as a natural antibacterial agent against Escherichia coli.